2021
DOI: 10.3390/ma14020333
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Influence of the High-Frequency Noise on the Results of Surface Topography Measurements

Abstract: The influence of errors in the processes of detection and then reduction of surface topography measurement noise is of great importance; many research papers are concerned with the definition of this type of measurement error. This paper presents the influence of high-frequency measurement noise, defined for various types of surface textures, e.g., two-process plateau-honed, turned, ground, or isotropic. Procedures for the processing of raw measured data as a detection of the high-frequency errors from the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…Appertaining to the results obtained in previous studies and based on the modeled data, it was found that the presence of the high-frequency noise affects the values of selected surface topography parameters, defined as ‘noise-sensitive parameters’ (NSP) [ 18 ], to a much greater extent than other parameters. The following parameters have been highlighted as an NSP: Sz , Sdq , Sdr , Spd , Spc, and Sk .…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Appertaining to the results obtained in previous studies and based on the modeled data, it was found that the presence of the high-frequency noise affects the values of selected surface topography parameters, defined as ‘noise-sensitive parameters’ (NSP) [ 18 ], to a much greater extent than other parameters. The following parameters have been highlighted as an NSP: Sz , Sdq , Sdr , Spd , Spc, and Sk .…”
Section: Resultsmentioning
confidence: 81%
“…Usually, differences for special parameters ( Sal , Str , Std ) were under 5% or were negligible, and when hybrid parameters were considered, the differences for root mean square gradient ( Sdq ) were slight. Nonetheless, all of those four parameters were defined previously as robust for the presence of the (high-frequency) noise [ 18 ]. Parameters related to the characterization of the peaks ( Spd , Spc ) underwent the greatest changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is extensive ongoing research to reduce the impact of noise and environmental disturbances on optical instruments. Examples of this for CSI can be found in [ 6 , 7 ]. Even if the reliability issues with optical instruments were to be solved, they would probably remain expensive even in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The various frequency characteristic components result in different impacts on the operation of the ultra-precise shafts due to the manufacturing errors on the components' surfaces [6]. As well as measurement and analysis of the surface topography of an engine cylinder-as a fingerprint of the manufacturing process [7]-it is also necessary to assess its meso-and macro-features: roundness and cylindricity.…”
Section: Introductionmentioning
confidence: 99%